2002
DOI: 10.1038/sj.hdy.6800103
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity and female-biased mutation at a microsatellite locus in the olive ridley sea turtle (Lepidochelys olivacea)

Abstract: Multiple paternity in the olive ridley sea turtle (Lepidochelys olivacea) population nesting in Suriname was demonstrated using two microsatellite loci, viz., Ei8 and Cm84. The large number of offspring sampled per clutch (70 on average, ranging from 15 to 103) and the number of alleles found at the two loci (18 and eight alleles, respectively) enabled unambiguous assessment of the occurrence of multiple paternity. In two out of 10 clutches analysed, the offspring had been sired by at least two males, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 28 publications
1
41
1
1
Order By: Relevance
“…One school of thought maintains that multiple paternity may buffer against the loss of allelic diversity by increasing the effective population size (Sugg & Chesser 1994, Newcomer et al 1999, Martinez et al 2000, Hoekert et al 2002. This is countered by theoretical results indicating that by increasing the variance in male reproductive success (because each mating may result in fewer offspring per male than with genetic monogamy), multiple paternity will reduce effective population size and, consequently, limit population genetic diversity (Nunney 1993, Ramakrishnan et al 2004, Karl 2008.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 57%
“…One school of thought maintains that multiple paternity may buffer against the loss of allelic diversity by increasing the effective population size (Sugg & Chesser 1994, Newcomer et al 1999, Martinez et al 2000, Hoekert et al 2002. This is countered by theoretical results indicating that by increasing the variance in male reproductive success (because each mating may result in fewer offspring per male than with genetic monogamy), multiple paternity will reduce effective population size and, consequently, limit population genetic diversity (Nunney 1993, Ramakrishnan et al 2004, Karl 2008.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 57%
“…Male-biased mutation has also been found in plants (Filatov and Charlesworth 2002;Whittle and Johnston 2002). The only example of female-biased mutation we are aware of is at a microsatellite locus in a sea turtle (Hoekeert et al 2002). Sex-biased mutation has not been found in other groups, including Drosophila (Bauer and Aquadro 1997), and it is not clear at present what the taxonomic distribution of the phenomenon is.…”
mentioning
confidence: 89%
“…Previous studies have demonstrated that the frequency of MP varies both between (Moore & Ball, 2002;Hoekert et al, 2002;Crim et al, 2002;Theissinger et al, 2008;Noble et al, 2013), and within species (Galbraith, 1993;FitzSimmons, 1998;Ireland et al, 2003;Jensen et al, 2006;LaBrecque et al, 2014). For green turtles, evidence of MP has been reported in several studies, but the proportion of clutches with MP varies among populations.…”
Section: Introductionmentioning
confidence: 96%